Influence of cooking duration on carotenoids, physical properties and in vitro antioxidant capacity of pasta prepared from three Canadian durum wheat cultivars. (30th November 2021) - Oduro-Obeng, Hannah; Fu, Bin Xiao; Beta, Trust
Highlights: Three durum whole wheat and semolina pasta were boiled to al dente, fully or overcooked. Contrary to the trans carotenoids, cis isomers significantly increased with increasing cooking duration. Pasta cooking loss increased while firmness decreased with increased cooking duration. Whole wheat pasta had significantly high antioxidant capacity regardless of cooking duration. Abstract: This study investigates the impact of different pasta cooking durations ( al dente, fully cooked or overcooked) on the carotenoid content and physical properties of whole wheat and refined semolina pasta prepared from three Canadian durum wheat cultivars. Carotenoids were analyzed using HPLC and spectrophotometry. Generally increasing cooking duration non-significantly increased lutein, zeaxanthin, total carotenoids, significantly increased the cis carotenoids but decreased carotenoid retention and firmness regardless of flour type or wheat cultivar. Despite this decrease, whole wheat pasta was significantly firmer than semolina when overcooked regardless of wheat cultivar. Antioxidant capacity was highly influenced by flour type but did not show a clear trend with cooking duration. Overall analysis indicates that increasing cooking duration of whole wheat or semolina pasta above 7 or 8 mins respectively allows for the maximum extraction of carotenoids with possible accessibility by digestive enzymes when consumed but this affects cooking quality including high cooking loss.